2020
DOI: 10.5194/acp-2020-274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remote sensing of methane leakage from natural gas and petroleum systems revisited

Abstract: Abstract. The switch from the use of coal to natural gas or oil for the energy generation potentially reduces the greenhouse gas emissions and thus the impact on global warming and climate change because of the larger energy content per CO2 molecule emitted. However, the climate benefit over coal is offset by methane (CH4) leakage from natural gas and petroleum systems, which reverses the climate impact mitigation if the rate of fugitive emissions exceeds the compensation point at which the global warming resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 26 publications
3
35
1
Order By: Relevance
“…Many studies have demonstrated the capabilities of satellite observations to estimate CH 4 emissions, e.g., from oil and gas sector, including accidental leakages (e.g., Varon et al, 2019;De Gouw et al, 2020;Schneising et al, 2020) and from coal mining (Varon et al, 2020). Launched in October 2017, the TROPOspheric Measuring Instrument (TROPOMI) on board the Copernicus Sentinel-5 Precursor satellite provides complete daily global coverage of CH 4 with an unprecedented resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated the capabilities of satellite observations to estimate CH 4 emissions, e.g., from oil and gas sector, including accidental leakages (e.g., Varon et al, 2019;De Gouw et al, 2020;Schneising et al, 2020) and from coal mining (Varon et al, 2020). Launched in October 2017, the TROPOspheric Measuring Instrument (TROPOMI) on board the Copernicus Sentinel-5 Precursor satellite provides complete daily global coverage of CH 4 with an unprecedented resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Launched in October 2017, the TROPOspheric Measuring Instrument (TROPOMI) on board the Copernicus Sentinel-5 Precursor satellite provides complete daily global coverage of CH 4 with an unprecedented resolution. Compared to previous satellite instruments, TROPOMI is able to capture CH 4 enhancements due to emissions on fine scales and to detect large point sources (Varon et al, 2019;De Gouw et al, 2020;Schneising et al, 2020). Satellite retrievals using thermal infrared nadir spectra as observed by IASI (Infrared Atmospheric Sounding Interferometer) or TES (Tropospheric Emission Spectrometer) are especially sensitive to CH 4 concentrations between the middle troposphere and the stratosphere (e.g., Siddans et al, 2017;García et al, 2018;De Wachter et al, 2017;Kulawik et al, 2021;Schneider et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…These conservative approaches still result in mean loss rate estimates over 8% with a 5 th percentile estimate never falling below 5.2%. (6,7,9). Applying our basin-wide quantification method to data from Cusworth et al in the overlapping region of New Mexico, we find a fractional loss rate of 4.4% for directlymeasured emissions (10).…”
Section: Airplane-detectable Emitters Drive Total Emissionsmentioning
confidence: 84%
“…With aircraft-and tower-based methane concentration measurements, Lyon et al estimated the NG production loss at 3.3% in a subdomain of the Permian (7). Zhang et al and Schneising et al apply inversion methods based on satellite measurements, finding a NG production loss rate of roughly 3.7% for the full Texas and New Mexico Permian (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…Intra-daily and inter-daily variation can be signicant; differences in emission rates recorded for an abandoned well can vary by a factor of 18 over a day 81 and similarly for whole oil and gas elds. 82 All measurement technologies will fall victim to these types of variation, with some well suited to capturing intra-daily variation (enclosed chamber, perimeter facility, micrometeorological, remote observatories and towers). But without signicant investment of time and money few are capable of accounting for inter-daily variation.…”
Section: Comparison To Other Technologiesmentioning
confidence: 99%